Subclinical lower limb Peripheral Arterial Disease in Patients with Type 2 Diabetes Mellitus: A cross-sectional study. - Fahad Naim; Syeda Hijab Amjad; Awais Naeem; Nizamuddin Utmani; Amjad Taqweem; Khattak , Rub Nawaz; Wasim Ahmad (International Journal of Endorsing Health Science Research, 2023)
Background: Peripheral artery disease (PAD) is highly prevalent in patients with diabetes mellitus. The ankle-brachial index (ABI) measurement is used to diagnose peripheral arterial disease, and little is known about its prevalence in asymptomatic type 2 Diabetic patients. This study aimed to determine the prevalence of subclinical peripheral artery disease in patients with type II diabetes mellitus. Methodology: It was a descriptive study conducted at the Peshawar Institute of Medical Sciences, from Feb 2022 to Aug 2022. Two hundred sixty-four patients with type II diabetes (for more than three years) with no clinical features of peripheral arterial disease were assessed by measuring ankle brachial pressure index for subclinical peripheral arterial disease. Reading less than 0.9 was positive for peripheral artery disease in the lower limbs. Results: Peripheral Arterial Disease was present in 115 (43.6%) patients and absent in 149 (56.4%) patients. The peripheral artery disease was significantly more in males, those with age greater than 55 years, smokers, and hypertensive patients (p-value ≤ 0.05) but was not associated with the duration of diabetes or BMI of the patient (p-value > 0.05) Conclusion: There was a high prevalence of asymptomatic peripheral artery disease in Type 2 Diabetic patients using ankle-brachial pressure index measurement. Those with ages greater than 55 years, smokers, hypertensive, and males were particularly at higher risk.